Fewer out-of-sequence vaccinations and reduction of child mortality in Northern Ghana. Issue 18 (25th April 2017) - Welaga, Paul; Oduro, Abraham; Debpuur, Cornelius; Aaby, Peter; Ravn, Henrik; Andersen, Andreas; Binka, Fred; Hodgson, Abraham
Highlights: We examined whether mortality is higher when DTP is the last vaccine compared to MV. Receiving DTP with or after MV was associated with higher mortality than MV after DTP. OPV campaigns reduced the mortality associated with receiving DTP with or after MV. The reduction in out-of-sequence vaccinations contributed to reducing mortality. The sequence of vaccinations is likely to be important for overall child mortality. Abstract: Background: Studies suggest that diphtheria-tetanus-pertussis (DTP) vaccine administered simultaneously with measles vaccine (MV) or DTP administered after MV are associated with higher child mortality than having MV-after-DTP3 as most recent vaccination. We tested this in Northern Ghana where the prevalence of such out-of-sequence vaccinations has declined. Methods: Using annual cohort data of children aged 12–23 months from 1996 to 2012 and Cox proportional hazards models, we assessed survival in relation to the most recent vaccination status within the next 12 months and until five years of age. We assessed whether mortality in children aged 12–59 months was higher when the most recent vaccine was non-live (DTP) rather than live (MV or OPV). Results: Out-of-sequence vaccinations with DTP-containing vaccines and MV declined from 86% in 1989 to 24% in 1996 and 0.7% in 2012. Between 1996 and 2012, 38 070 children had their vaccinations status assessed: the adjusted hazard ratio (HR) for out-of-sequence vaccinations (DTP >= MV) compared with the recommended sequence of MV-after-DTP3 was 1.42(1.06–1.90) during the first 12 months after assessment of vaccination status and 1.29(1.03–1.60) with follow-up to five years of age; the HR was 2.58(1.14–5.84) before OPV or MV campaigns and 1.37(1.02–1.85) after the campaigns. Conclusion: Out-of-sequence vaccinations with DTP and MV are associated with higher mortality than MV as most recent vaccination; the effect is unlikely to be due to confounding. Hence, the reduction in out-of-sequence vaccinations may have lowered child mortality. It is recommended not to give DTP with MV or DTP after MV.